Ability of phenolic acids to protect naturally present alfa-tocopherol during the heating of plant oils - Zuzana RÉBLOVÁ; Jakub FIŠNAR; Dana TICHOVSKÁ; Marek DOLEŽAL; Kristýna JOUDALOVÁ (Czech Journal of Food Sciences, 2012)
The ability of phenolic acids (ferulic, gallic, protocatechuic, and sinapic; 600 mg/kg) to protect naturally present a-tocopherol was tested during the heating of sunflower oil on a hot plate set at 120, 150, 180, 210, or 240°C, and during the heating of rapeseed, olive and soybean oils on a hot plate set at 180°C. In all the studied conditions, a-tocopherol was significantly protected only by gallic acid. This phenolic acid prolonged the half-life of a-tocopherol (calculated as the time needed for the a-tocopherol content to decrease to 50% of the original value) typically two- to four-fold. Hence the ability of phenolic acids to protect a-tocopherol in bulk oils does not markedly depend on the experimental conditions as is seen in antioxidant activity, i.e. in the ability of antioxidants to protect fatty acids.